Hak dan Kewajiban Warga Negara: Tinjauan Pelaksanaan dan Implikasinya Berdasarkan UUD 1945 - Shinta Shavira; Syariah Syariah; Okti Nurvadila; Erdi Saputra (International Forum of Researchers and Lecturers, 2025)
Citizens' rights and obligations are the main pillars in building a balanced and just national and state life. In the 1945 Constitution of the Republic of Indonesia, rights and obligations are strictly regulated to ensure the creation of order, welfare, and active participation of citizens in national development. However, in its implementation, there are still inequalities, especially the lack of public awareness of the implementation of obligations, such as obedience to the law, defending the country, and respecting the rights of others. This study aims to examine how the implementation of citizens' rights and obligations takes place and their impact on community, national, and state life. The method used is a literature review with a descriptive qualitative approach. The results of the study indicate that there is a need to strengthen civic education, increase exemplary behavior from the government, and enforce fair law in order to create a balance between rights and obligations according to the mandate of the 1945 Constitution. Collective awareness between the government and citizens is very necessary in order to achieve a democratic and civilized life order.